(untitled) (University of Khartoum Journal of Agricultural Sciences, 2021)
The effectiveness of selection in any cropdepends on the magnitude of the available genetic variability in the gene pool of the species. In this study, 12 cowpea genotypes (ten accessions and two check cultivars) were assessed for agronomic performance, extent of genetic variability and the association between different traits. The genotypes were sown in two consecutive seasons (October 2015/2016 and 2016/2017) at Shambat using a randomized complete block design with three replicates. Agronomic performance, variance components, genetic coefficient of variation, heritability, genetic advance and genotypic and phenotypic correlation coefficients were estimated. The genotypes exhibited wide variation in all of the studied traits. Seed yield ranged from 477.71 (genotypeHSD-5674) to 2204 kg/ha (genotypeHSD-5131).Highest estimates of genetic coefficient of variation (48.98) and genetic advance as percentage of the mean (81.21) were obtained for number of pods/plant and seed yield/plant, whereas days to maturity showed the lowest estimates. However, days to maturity had the highest heritability estimate (86%) and seed yield/plant had the lowest (40%) value. Seed yield (Kg/ha)had significant positive genotypic and phenotypic association with each of seed yield/plant, number of pods/peduncle and number of pods/plant indicating that selection for these traits may be effective in yield improvement of the present cowpea genotypes. Genotypes HSD-5131, HSD-5130 and HSD-5672 appeared promising for future seed yield improvement breeding programs under the semi-tropics of Sudan